CLINICAL AND PARACLINICAL CHARACTERISTICS OF PATIENTS WITH URINARY TRACT INFECTIONS AND ASSOCIATED FACTORS AT THAI NGUYEN NATIONAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and paraclinical characteristics of patients with urinary tract infections (UTIs) and analyze some factors related to urine culture results.Subjects and Methods: A cross-sectional descriptive study was conducted on 52 patients diagnosed with UTI at the Department of Nephrology – Urology and Hemodialysis, Thai Nguyen National Hospital, from January 2025 to October 2025. Related factors were analyzed using the Chi-square test, calculating Odds Ratio (OR) with a 95% confidence interval; p
Keywords: Urinary tract infection, Urine culture, Urinary nitrite, C-reactive protein, Antibiotic resistance.